2021
DOI: 10.1186/s12981-021-00338-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of failure on second-line antiretroviral therapy with protease inhibitor mutations in Uganda

Abstract: Introduction Failure on second-line antiretroviral therapy (ART) with protease inhibitor (PI) mutations (VF-M) is on the rise. However, there is a paucity of information on the factors associated with this observation in low-income countries. Knowledge of underlying factors is critical if we are to minimize the number of PLHIV switched to costly third-line ART. Our study investigated the factors associated with VF-M. Methods We conducted a matched … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Being on anti-TB treatment and second-line treatment failure was positively associated, which is supported by studies conducted in Ethiopia and Uganda [ 21 , 24 ]. In line with this, studies showed that having an advanced clinical condition at treatment switch is a risk for treatment failure [ 8 , 9 , 21 , 22 ] and adverse drug reaction [ 25 ].…”
Section: Discussionmentioning
confidence: 56%
“…Being on anti-TB treatment and second-line treatment failure was positively associated, which is supported by studies conducted in Ethiopia and Uganda [ 21 , 24 ]. In line with this, studies showed that having an advanced clinical condition at treatment switch is a risk for treatment failure [ 8 , 9 , 21 , 22 ] and adverse drug reaction [ 25 ].…”
Section: Discussionmentioning
confidence: 56%
“…never reported tuberculosis co-infection as an independent predictor of a second-line switch, it was documented as the primary cause of first-line treatment failure [31,32]. This could be rationalized as tuberculosis infection facilitates viral replication by activating the immune system, which leads to viral load increment.…”
Section: Plos Onementioning
confidence: 99%
“…1 Uganda, one of the 10 high-burden countries in Sub-Saharan Africa, had a nationwide HIV prevalence of 6.2% among 15–49-year-olds in 2018, with the South-Western region having the country’s second highest HIV prevalence at 7.9%, with 7.6% among females and 4.7% among males. 2 …”
Section: Introductionmentioning
confidence: 99%